2012
DOI: 10.1111/j.1439-0310.2012.02042.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variation in Note Composition and Use ofchick‐a‐deeCalls of Carolina Chickadees (Poecile carolinensis)

Abstract: The aim of this study was to determine whether geographic variation exists in the composition of note types in the chick‐a‐dee call of Carolina chickadees. This determination is of interest for two reasons: earlier studies with a related species suggested minimal geographic variation in note composition, and geographic variation in social signals may represent important developmental or selection processes shaping signal use. Carolina chickadees were recorded in a naturalistic observation study in west‐central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…This is consistent with previous studies showing that parids are often followed by other species that exploit the same food items [4]. In general, parids have large vocal repertoires [41,42] and produce different call types in different contexts, such as when driving away a predator [4345] or when in flight [46]. These calls may be recognized by other species and evoke behavioural responses [1214], but the community-level outcomes of interspecific communication remain poorly understood [3].…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with previous studies showing that parids are often followed by other species that exploit the same food items [4]. In general, parids have large vocal repertoires [41,42] and produce different call types in different contexts, such as when driving away a predator [4345] or when in flight [46]. These calls may be recognized by other species and evoke behavioural responses [1214], but the community-level outcomes of interspecific communication remain poorly understood [3].…”
Section: Discussionsupporting
confidence: 90%
“…In most Poecile and Baeolophus species, D notes are used more often in higher arousal contexts such as predation threat. D notes are rarely used in flight, at least in Carolina chickadees (Freeberg & Mahurin, ). We suspect that D note usage by bridled titmice will be similar to that seen in other Paridae species.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, during recording, the observer noted whether bridled titmice produced calls in the context of ‘flight’ or of ‘close interaction’. The context of flight included calls produced by a signaler while it was flying and calls that were produced within 1 s of leaving a perch to take flight (as in studies of Carolina chickadees: Freeberg, ; Freeberg & Mahurin, ). We defined ‘close interaction’ when two bridled titmice were within 15 cm of one another.…”
Section: Methodsmentioning
confidence: 99%
“…); the humpback whale, Megaptera novaeangliae (Garland et al . ); and the calls of the Carolina chickadee, Poecile carolinensis (Freeberg ) , to reconstruct geographical dialect. In the case of the hyrax, humpback whale and chickadee, the calls consisted of a sequence of discrete acoustic elements.…”
Section: Methodsmentioning
confidence: 99%
“…), the second data set used recordings of rock hyraxes (Kershenbaum et al . ) and the third set Carolina chickadees (Freeberg ). Previous studies have shown that in the humpback whale, rock hyrax and Carolina chickadee, song syntax varies according to the geographical origin of the population.…”
Section: Methodsmentioning
confidence: 99%